Risk Factors for Post-Stroke Seizures in a Tertiary Care Center: A Case–Control Study - Mohamed AA; Tan JK; Tan MM; Khoo CS; Wan Yahya WNN; Abd Rahman MSH; Sutan R; Tan HJ (Neuropsychiatric Disease and Treatment, 2024)
Aminath Afaa Mohamed,1,2 Juen Kiem Tan,1,2 Michelle Maryanne Tan,3 Ching Soong Khoo,1,2 Wan Nur Nafisah Wan Yahya,1,2 Muhammad Samir Haziq Abd Rahman,2 Rosnah Sutan,2,4 Hui Jan Tan1,2 1Department of Medicine, Faculty of Medicine, National University of Malaysia, Kuala Lumpur, 56000, Malaysia; 2Department of Medicine, Hospital Canselor Tuanku Muhriz, Cheras, Kuala Lumpur, 56000, Malaysia; 3Department of Medicine, Hospital Tengku Ampuan Rahimah, Klang, 41200, Malaysia; 4Department of Community Health, Faculty of Medicine, National University of Malaysia, Kuala Lumpur, 56000, MalaysiaCorrespondence: Hui Jan Tan, Department of Medicine, Faculty of Medicine, National University of Malaysia, Kuala Lumpur, Malaysia, Email tanhuijan@gmail.com; tanhuijan@ukm.edu.myPurpose: Stroke is the second leading cause of global deaths. Post-stroke seizures (PSS) can lead to lasting complications, such as prolonged hospitalizations, increased disability rates, and higher mortality. Our study investigates the associated factors that contribute to post-stroke seizures in patients at a local tertiary hospital.Patients and Methods: We designed a case–control study where patients admitted with PSS were recruited with consent. Controls admitted for stroke without seizure were then included. Suitability based on exclusion criteria was ensured before recording their sociodemographic and clinical data. An EEG was performed and read by two certified neurologists before the data was analyzed.Results: We recruited 180 participants, 90 cases and 90 matched controls. Gender (p=0.013), race (p=0.015), dyslipidemia (p< 0.001), prior stroke (p< 0.031), large artery atherosclerosis (p< 0.001), small vessel occlusions (p< 0.001), blood pressure on presentation (p< 0.028) and thrombolysis administration (p< 0.029) were significantly associated with the occurrence of PSS. An increase in odds of PSS was observed in the male gender (1.974), dyslipidemia (3.480), small vessel occlusions (4.578), and in participants with epileptiform changes on EEG (3.630). Conversely, lower odds of PSS were seen in participants with high blood pressure on presentation (0.505), large artery atherosclerosis (0.266), and those who underwent thrombolysis (0.319).Conclusion: This study emphasized that identifying post-stroke seizures may be aided by EEGs and recognizing at-risk groups, which include males of Chinese descent in Asia, dyslipidemia, small vessel occlusions, those with low to normal blood pressure on presentation, and epileptiform changes in EEGs.Plain Language Summary: The research aims to establish the risk factors associated with post-stroke seizures in an Asian population and their similarity to the Western literature. Our findings highlight the critical risk factors to identify in at-risk patients, which may prompt changes in guidelines in future to enhance patient outcomes and improve the quality of care.Keywords: seizures, stroke, post-stroke epilepsy, epilepsy, electroencephalogram